STUDY ON THE MANAGEMENT OF THE SACRED AREA OF TARO VILLAGE AS EDUCATIONAL TOURISM - Anak Agung Gede Rai Astawa (Ride: Journal of Cultural Tourism and Religious Studies, 2025)
This study explores the multifaceted challenges and impacts of tourism management in Taro Village, Bali, with a specific focus on sacred areas such as Gunung Raung Temple and the Lembu Putih Conservation Park. One of the primary challenges identified is the lack of financial incentives for the Pokdarwis (Tourism Awareness Group) administrators and field officers, which affects their motivation and service delivery. Despite these limitations, the village has established a distinctive revenue model—where Gunung Raung Temple operates on a donation basis, and the Lembu Putih Conservation Park charges admission, with profits reinvested in community development. The sacred areas play a significant role in promoting educational tourism, offering visitors insights into Balinese spiritual traditions and environmental conservation. Traditional ceremonies such as Tegenan, Mepada Agung, and Nyenuk are central to Taro’s cultural identity and spiritual appeal. The study also evaluates the positive and negative impacts of tourism using various theoretical frameworks, including economic, sociocultural, environmental, and ethical tourism. While minor drawbacks exist, the predominant outcomes are positive, including improved environmental management, increased local employment, and strengthened cultural preservation. The findings underscore the importance of community involvement and sustainable tourism practices, aligned with the principles of Community-Based Tourism (CBT), to ensure long-term benefits for both the village and its sacred heritage.